Cover Feature: Total Synthesis, Stereochemical Assignment, and Divergent Enantioselective Enzymatic Recognition of Larreatricin (Chem. Eur. J. 59/2018). Issue 59 (18th October 2018) - Martin, Harry J.; Kampatsikas, Ioannis; Oost, Rik; Pretzler, Matthias; Al‐Sayed, Emir; Roller, Alexander; Giester, Gerald; Rompel, Annette; Maulide, Nuno
Abstract : Mirror, mirror on the wall, who is the fairest one of all? Larreatricin is a naturally occurring lignan with a long history of use in traditional medicine. However, its absolute configuration remains unknown and its biological activity is poorly understood. An efficient total synthesis allowing for the unambiguous assignment of the configuration of its enantiomers is presented. Polyphenol oxidases show high and remarkably divergent enantioselective recognition of this secondary metabolite. More information can be found in the Communication by H. J. Martin, A. Rompel, N. Maulide et al. onpage 15756 .